2016
DOI: 10.1080/08927014.2016.1261847
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Listeria monocytogenes dual-species biofilms using combined enzyme-benzalkonium chloride treatments

Abstract: Type of publicationArticle (peer-reviewed)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 74 publications
4
17
0
Order By: Relevance
“…To our knowledge, the effect of commercial enzymatic agents on L. monocytogenes biofilms has not been reported before. However, the results were in the same range as in two previous studies on biofilm removal using enzymes, resulting in a modest reduction of 1-2 log 10 reduction [22,34]. As stated in Section 3.2, the literature shows highly variable results for the effect of commercial alkaline cleaners on L. monocytogenes biofilms.…”
Section: Examining the Efficacy Of Enzyme-based Cleaning For Biofilm supporting
confidence: 72%
“…To our knowledge, the effect of commercial enzymatic agents on L. monocytogenes biofilms has not been reported before. However, the results were in the same range as in two previous studies on biofilm removal using enzymes, resulting in a modest reduction of 1-2 log 10 reduction [22,34]. As stated in Section 3.2, the literature shows highly variable results for the effect of commercial alkaline cleaners on L. monocytogenes biofilms.…”
Section: Examining the Efficacy Of Enzyme-based Cleaning For Biofilm supporting
confidence: 72%
“…This study demonstrated that the most effective treatment against mixed biofilms was the one obtained using DNase, followed by pronase and cellulase, achieving a disaggregation of 2 log CFU cm −2 . Rodríguez-López, Carballo-Justo, Draper, and Cabo (2017) followed the same line of research, showing that the sequential application of pronase first and then benzalkonium chloride at appropriate doses was a potential strategy for controlling pathogens on food contact surfaces.…”
Section: Evaluation Of the Biofilm By The Culture Methodsmentioning
confidence: 93%
“…For mixed species biofilm of L. innocua FI 2 with L. plantarum PC 1.2, we showed that both strains were more resistant to all tested disinfectants than in single species, which concurs with previous work performed by, for example, Saá Ibusquiza, Cabo, and Herrera (2010), who showed the increased resistance of L. monocytogenes to BAC when grown in a co-culture with Pseudomonas putida on the stainless steel surface. In another study, L. monocytogenes exhibited an increased resistance to BAC when grown in the mixed species biofilms with Escherichia coli (Rodríguez-López, Carballo-Justo, Draper, & Cabo, 2017). Many studies suggest that interspecies interaction caused higher resistance of strains in mixed species biofilms than in single species (Millezi et al, 2012), but there are known also antagonistic interactions (Boari, Alves, Reis, Savian, & Piccoli, 2009;Rao, Webb, & Kjelleberg, 2005).…”
Section: Discussionmentioning
confidence: 99%